Assessment of Homeroom Adviser’s Role on School Family Involvement in Senior High School in Manila (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
Teachers have a vital role in bridging the gap between school and home. Pupils' success is determined by their connection to the educational process. Parental involvement may help students improve their behavior, participation, and achievement. School and community collaborations may also help to improve, assist, and even change learners and individual partners to improve program quality, resource efficiency, and goal alignment. In this instance, Republic Act No. 9155 requires school leaders to have power, accountability, and responsibility in the school and community. The goal of this descriptive research was to assess the roles of homeroom advisers in school-family involvement. The research questioned 375 parents in grade 12 from a selected Senior High School in District VI of Manila. It aimed to examine the degree to which homeroom advisers play a role in school-family involvement as seen by parent respondents for families to participate in school planning, leadership, and volunteering. The overall mean result of the evaluation on the degree to which homeroom advisers affect school-family involvement is involved. The highest indication of respondent's evaluation of the degree of Homeroom Advisers' Role in school-family involvement is Information to families to assist their children's learning, while the lowest indicator is Opportunities for families in school planning, leadership, and volunteer activities. The research recommended that the homeroom adviser's handbook include information on parental involvement in school, planning, leadership, and volunteer activities to increase parents' commitment to high-quality education.